Mobility in Older Community-Dwelling Persons: A Narrative Review - Freiberger, Ellen; Sieber, Cornel Christian; Kob, Robert (Frontiers in Physiology, 2020)
Due to the demographic changes and the increasing awareness of the role of physical function, mobility in older age is becoming an important topic. Mobility limitations have been reported as increasingly prevalent in older persons affecting about 35% of persons aged 70 and the majority over 85 years. Mobility limitations have been associated with increased fall risk, hospitalization and even mortality and a decreased quality of life. As concepts of mobility are multifactorial and complex, in this narrative review, physiological, psychological and environmental aspects contributing to mobility limitations will be presented for a holistic understanding. Assessment of mobility as well as exercise interventions are shortly addressed.